1991
DOI: 10.1007/bf02493518
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacologic correlates of deglutition: Lessons from fictive swallowing

Abstract: Pharmacologic investigations into the transmission processes underlying fictive swallowing in the rat have disclosed the potential diversity of chemical signals used in central deglutitive pathways. Monoaminergic mechanisms appear to serve as links between subcortical structures and the medullary pattern generator of swallowing (PGS), and may play a critical role in maintaining internal facilitatory drive, required by the PGS for optimal responsivity to peripheral sensory input. Cholinergic bulbar interneurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 81 publications
(163 reference statements)
1
39
0
Order By: Relevance
“…They mediate many of the afferent or descending signals that initiate these behaviors, which include locomotion (43, 590), chewing (608), and deglutition (105). Furthermore, exogenous glutamate can activate a variety of episodic rhythmic behaviors.…”
Section: D) Role Of Glutamate In Transmission Of Rhythmic Motor Drivementioning
confidence: 99%
See 1 more Smart Citation
“…They mediate many of the afferent or descending signals that initiate these behaviors, which include locomotion (43, 590), chewing (608), and deglutition (105). Furthermore, exogenous glutamate can activate a variety of episodic rhythmic behaviors.…”
Section: D) Role Of Glutamate In Transmission Of Rhythmic Motor Drivementioning
confidence: 99%
“…GABA-and glycine-mediated postsynaptic inhibition of motoneuron activity also contributes significantly to production of rhythmic behaviors, including respiration (353,834), locomotion (201,486,644,968), chewing (207,337,538), and swallowing (105), where motoneuron activity is characterized by sequential phases of excitation and inhibition. Inhibitory synaptic control of excitability during the active phase will affect the timing of burst onset and offset (affecting onset of muscle contraction and relaxation), firing pattern, and recruitment order (961,969,1049,1377,1379).…”
Section: C) Presynaptic Actions Of Gaba a Receptorsmentioning
confidence: 99%
“…They were all Gray's type I terminals. Since swallowing and esophageal peristalsis is produced by coordinated synchronous muscle contractions (Miller, 1982;Bieger, 1984Bieger, , 1991, our results provide anatomical bases for the notion that the NTS inputs generate synchronized discharge on the esophageal motoneurons, which exert coordinated activity of the esophageal muscles.…”
Section: Discussionmentioning
confidence: 78%
“…There are multiple receptor sites within the pharynx, which bind pharmacological agents [78]. Anecdotal reports have suggested that both cisapride and nifedipine may aid those with mild-to-moderate dysphagia.…”
Section: Stroke and Swallowingmentioning
confidence: 99%